Подолання викликів постграмотності й диджиталізації у викладанні природничих дисциплін - Герасько, Тетяна Володимирівна; Gerasko, Tetyana (Запоріжжя : ТДАТУ, 2025)
UA: Диджиталізація сприяє зменшенню інформаційної ролі письмового тексту на користь візуальному і художньому контенту. Штучний інтелект полегшує рутинну роботу викладачів і студентів, проте створює етичні проблеми. Для подолання викликів постграмотності і диджиталізації при викладанні природничих дисциплін пропонується використовувати креативні завдання на основі критичного осмислення навчального матеріалу і відео- (фото-) звіти студентів з виконання ними практичних завдань. /// EN: Digitalization contributes to the reduction of the information role of written text in favor of visual and artistic content. Artificial intelligence facilitates the routine work of teachers and students, but creates ethical problems. To overcome the challenges of post-literacy and digitalization in teaching natural sciences, it is proposed to use creative tasks based on critical reflection on educational material and video (photo) reports of students performing practical tasks.
Overcoming the challenges of post-literacy and digitalization in teaching science subjects
Keywords: постграмотність; диджиталізація; інклюзивність освіти; природничі дисципліни; post-literacy; digitalization; inclusive education; natural sciences